El Palacio de la Novela (1930-1936). La Editorial Castro S.A. entre conservadurismo y compromiso - Jean-François Botrel (Cahiers de Civilisation Espagnole Contemporaine)
How, with the proclamation of the Second Republic in 1931, a publishing house fundamentally dedicated, since 1840, to the publication of popular novels and newly installed in a splendid «Palace of the Novel» in the suburbs of Madrid, reorients its production to adapt it and attend the new circumstance, until the end of the Civil War.